Between Mini-India and Sonar Bangla: the memorialisation and place-making practices of East Bengal Hindu refugees in the Andaman Islands - Zehmisch, Philipp (Partition and the practice of memory, 2018)
The post-Partition history of the Andaman Islands is represented as showcase project of Indian secularism. Settlement policies aiming to uplift subaltern refugees, repatriates and landless people were accompanied by labour migrations from all over South Asia. In nationalist speak, this multi-ethnic and multi-religious society is designated as ‘Mini-India’ and stands as exemplary for the communal ‘harmony’ of 400,000 Andaman residents. The state-directed rehabilitation of 3652 East Bengal Hindu refugee families as agricultural pioneers on forest lands was influenced by secularist policies. As a result, Bengali settlers—coming both after Partition and the 1971 war—have adapted to their new homelands by appropriating the values, norms and practices of Mini-India. Moreover, their place-making processes have been accompanied by an ethno-history composed of a nostalgia for their lost homelands in Sonar Bangla (Golden Bengal) as well as memories of violence and deprivation. Refugee settlers thus display a hybrid diasporic belonging encompassing both localised ‘Indian-ness’ and trans-local ‘Bengali-ness’. My chapter will highlight the ways in which the trope of Bengal becomes efficacious in the present Andaman society. I will concentrate on three dimensions of memorisation: first, Andaman ‘Bengali-ness’ can be regarded as a dynamic sociocultural and ecological reconstruction involving an ‘ethnic’ transformation of the cultivated landscape, environment and infrastructure. Second, Bengalis adopt a political identification as nationalists by invoking the hegemonic memory of the anti-colonial struggle focussing on the infamous Andaman Cellular Jail as a site where Bengali freedom fighters suffered for the nation. Third, they refer to historical victimisation and deprivation when claiming affirmative action.
First Online: 06 December 2017
Gesehen am 14.12.2021